2013
DOI: 10.1103/physrevb.88.214108
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase-transition sequence in CoF2: An experimental and first-principles study on the crystal, vibrational, and electronic properties

Abstract: We report a complete structural study of CoF 2 under pressure. Its crystal structure and vibrational and electronic properties have been studied both theoretically and experimentally using first-principles density functional theory (DFT) methods, x-ray diffraction, x-ray absorption at Co K-edge experiments, Raman spectroscopy, and optical absorption in the 0-80 GPa range. We have determined the structural phase-transition sequence in CoF 2 and corresponding transition pressures. The results are similar to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 55 publications
4
37
1
Order By: Relevance
“…Interestingly, the lowest-frequency Ag mode (not observed experimentally) is predicted to soften upon compression. This behavior resembles the one found in compounds adopting at ambient conditions the rutile aristotype, for example ZnF2 [24], CoF2 [28,31], FeF2 [30], and MnF2 [33]. In these systems the pressure-induced softening of a low-frequency B1g mode leads to a second order phase transition from the P42/mnm structure to a CaCl2-type polymorph (Pnnm symmetry, Z = 2).…”
Section: Raman Scattering Up To 29 Gpasupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, the lowest-frequency Ag mode (not observed experimentally) is predicted to soften upon compression. This behavior resembles the one found in compounds adopting at ambient conditions the rutile aristotype, for example ZnF2 [24], CoF2 [28,31], FeF2 [30], and MnF2 [33]. In these systems the pressure-induced softening of a low-frequency B1g mode leads to a second order phase transition from the P42/mnm structure to a CaCl2-type polymorph (Pnnm symmetry, Z = 2).…”
Section: Raman Scattering Up To 29 Gpasupporting
confidence: 74%
“…This compound is one of the simplest binary connections containing the Cu 2+ cation. It belongs to the family of metal difluorides, which have been extensively studied at high pressure [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Due to the operation of the JT effect CuF 2 adopts at ambient conditions a rarely-encountered crystal structure found only in one other compound (CrF 2 ) [38].…”
Section: Introductionmentioning
confidence: 99%
“…For rutile structures (TiO2, CaCl2) it is equal to about 9 meV/GPa, while it is larger for the fluorite structures (21 meV/GPa) and PbCl2 (18 meV/GPa). These values are larger than reported for CoF2 (dEg/dp < 7 meV/GPa), 20 but smaller than for MgF2 (dEg/dp ≈ 40 meV/GPa). 17 These differences most likely stem from the different electronic configuration between Zn 2+ (3d 10 ), Co 2+ (3d 7 ) and Mg 2+ (2s 2 2p 6 ).…”
Section: Dft Calculationscontrasting
confidence: 64%
“…Numerous experimental and theoretical investigations were conducted in order to establish the phase sequence for these compounds. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The motivation for these studies was the fact that the behaviour of difluorides at these conditions can serve as an analogue of the high-pressure transformations of dioxides, in particular SiO2. 7,8 Moreover high-pressure studies on MF2 systems revealed a surprisingly wide range of structures adopted by these compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation